Technological Barriers to Adoption of Induction Stoves in Bhaktapur, Nepal - Bajracharya, Yogesh; Adhikari, Pujan (Economic Journal of Development Issues, 2022)
The relevance of providing access to clean cooking solutions is linked to several associated co[1]benefits that contribute to a wide range of Sustainable Development Goals (SDGs). Most of the households in urban areas of Nepal use liquefied petroleum gas (LPG) for cooking purposes along with a gradual introduction of electric induction stoves. The main objective of this research is to identify the technological barrier to the adoption of induction stoves. Primary data were collected from 300 households of Bhaktapur Municipality and Madhyapur Thimi Municipality in March 2021. The result shows that a total of 27 percent of households use induction stoves. Twenty six percent of households did not know about induction stoves and 47 percent of household were aware of induction stove despite not owning one themselves. The finding suggest that the need for special utensil and unable to cook multiple foods at a time are the major technological barrier to the adoption of induction stoves. The research also identifies that elevated initial costs and an inconsistent electricity supply pose significant barriers to the widespread adoption of induction stoves. The chi-square test further established a statistically significant relationship between ranking of barriers and the adoption of induction cooking. An awareness program should be launched to penetrate the use of induction stoves in Nepalese society. The study also suggests a reliable supply of electricity so that the consumer can rely completely on induction stoves for household cooking.